Giant room temperature ferromagnetism in rutile TiO 2 implanted by Co - (:unkn) unknown (My University, 2004)
Giant room temperature ferromagnetism has been observed, for the first time, in the Co ion- implanted rutile TiO 2. The Co ions have been accelerated to 40 keV and implanted into TiO 2 (100) and TiO 2 (001) substrates. Both as prepared and temperature annealed samples were studied by magnetic resonance technique in the temperature range of 4-300 K. Strongly anisotropic ferromagnetic resonance (FMR) signals have been observed in the as prepared (100) and (001) TiO 2 samples. The theoretical analysis of FMR data has revealed rhombic magnetic anisotropy energy for Co-doped rutile TiO 2. The temperature annealing drastically affects the magnetic properties of the samples resulting in disappearance of the ferromagnetism and formation of paramagnetic Co 2+ centers. © 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.